(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
In the context of rapid changes in the global tourism market, innovations are becoming a key factor in increasing the competitiveness and sustainability of enterprises in the industry. The article examines the role of innovative solutions in the process of adapting tourism services to changing consumer needs, the development of digital technologies and the transformation of the global economic environment. Particular attention is paid to the introduction of digitalization, personalized services and sustainable practices that allow tourism companies to quickly respond to market challenges and form long-term advantages. The analysis shows that innovative activities not only help to meet the increased demands of customers, but also open up new opportunities for diversifying the tourism product, improving the quality of service and strengthening consumer confidence.